Effect of Bio-fertilizers on Growth of Terminalia chebula Retz. Seedlings in Nursery - Sivalingam, R.; Smitha, M.; Hegde, Maheshwar; Karthikeyan, A.; Palanisamy, K. (Indian Forester, 2010)
Response of Terminalia chebula Retz. To application with three different Biofertilizers like Azospirillum, phospobacteria and vesicular arbuscular mycorrhizal (VAM) and four different Biofertilizers combinations like Azospirillum with Phospobacteria, Azospirillum with VAM Phospobacteria with VAM and Azospirillum with Phospobacteria and VAM was studied under nursery condition. The plants were assessed for increment in height, stem girth, collar diameter and number of leaves at 30, and 60 days of treatment. The treatment with combination of Azospirillum 5g + Phospobacteria 5g to polythene bags (22 Ã— 15 cm) containing soil, sand and FYM (2:1:1) showed higher growth in height, stem girth and root collar diameter. Seedling treated with VAM also had greater shoot and leaf biomass. The use of Biofertilizers such as Azospirillum, Phospobacteria and Vesicular Arbuscular Mycorrhizal fungi (VAM) on Terminalia chebula to solve the problem of slow growth of seedlings is discussed.